Generational accounting, solidarity and pension losses - Coen N. Teulings; Casper G. de Vries (Institute for the Study of Labor (IZA), 2003)
The creeping stock market collapse eroded the wealth of funded pension systems. This led to political tensions between generations due to the fuzzy definition of property rights on the pension funds wealth. We argue that this problem can best be resolved by the introduction of generational accounts. Using modern portfolio and consumption planning theory we show that the younger generations should have the higher equity exposure due to their human capital. Capital losses should be distributed smoothly over lifetime consumption. When stock markets are depressed equity should be bought, savings and consumption should be scaled down equiproportionally, and retirement should be postponed. Portfolio investment restrictions are quite costly.
Keywords: J32; H55; G23; G2; E2; 330; saving and investment; pension funds; private pensions; social security and public pensions; financial institutions; Pensionsfonds; Private Rentenversicherung; Börsenkrise; Gesetzliche Rentenversicherung; Intergenerative Belastungsrechnung; Solidarität; Generationenbeziehungen; Portfolio-Management; Theorie